Aldolase‐Catalyzed Asymmetric Synthesis of N‐Heterocycles by Addition of Simple Aliphatic Nucleophiles to Aminoaldehydes. Issue 11 (15th February 2019) - Roldán, Raquel; Hernández, Karel; Joglar, Jesús; Bujons, Jordi; Parella, Teodor; Fessner, Wolf‐Dieter; Clapés, Pere
Abstract: Nitrogen heterocycles are structural motifs found in many bioactive natural products and of utmost importance in pharmaceutical drug development. In this work, a stereoselective synthesis of functionalized N‐heterocycles was accomplished in two steps, comprising the biocatalytic aldol addition of ethanal and simple aliphatic ketones such as propanone, butanone, 3‐pentanone, cyclobutanone, and cyclopentanone to N ‐Cbz‐protected aminoaldehydes using engineered variants of d ‐fructose‐6‐phosphate aldolase from Escherichia coli (FSA) or 2‐deoxy‐d ‐ribose‐5‐phosphate aldolase from Thermotoga maritima (DERA Tma ) as catalysts. FSA catalyzed most of the additions of ketones while DERA Tma was restricted to ethanal and propanone. Subsequent treatment with hydrogen in the presence of palladium over charcoal, yielded low‐level oxygenated N‐heterocyclic derivatives of piperidine, pyrrolidine and N‐bicyclic structures bearing fused cyclobutane and cyclopentane rings, with stereoselectivities of 96–98 ee and 97:3 dr in isolated yields ranging from 35 to 79%. Abstract :